2017
DOI: 10.15171/bi.2017.05
|View full text |Cite
|
Sign up to set email alerts
|

Common chemotherapeutic agents modulate fatty acid distribution in human hepatocellular carcinoma and colorectal cancer cells

Abstract: Introduction: Cancer cells are critically correlated with lipid molecules, particularly fatty acids, as structural blocks for membrane building, energy sources, and related signaling molecules. Therefore, cancer progression is in direct correlation with fatty acid metabolism. The aim of this study was to investigate the potential effects of common chemotherapeutic agents on the lipid metabolism of hepatocellular carcinoma (HCC) and colorectal cancer (CRC) cells, with a focus on alterations in cellular fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…For example, doxorubicin and 5-fluorouracil treatment significantly increased the number of lipid droplets within HepG2 cancer cells. They also reported a significant increase in SFAs (PA) and PUFAs and a significant decrease in MUFAs (OA and PTA) following chemotherapy treatments in the phospholipid fractions of the membranes of cancer cells (93).…”
Section: Diet-induced Obesity Distinctly Alters Lipid Metabolism In Tmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, doxorubicin and 5-fluorouracil treatment significantly increased the number of lipid droplets within HepG2 cancer cells. They also reported a significant increase in SFAs (PA) and PUFAs and a significant decrease in MUFAs (OA and PTA) following chemotherapy treatments in the phospholipid fractions of the membranes of cancer cells (93).…”
Section: Diet-induced Obesity Distinctly Alters Lipid Metabolism In Tmentioning
confidence: 95%
“…However, the authors explained that it is still unknown whether the suppression of adipose tissue lipid storage capacity induced by chemotherapy is a result of decreased HSL expression, or due to mitochondrial dysfunction induced by the chemotherapy (92). Mehdizadeh et al (93) showed that doxorubicin and 5-fluorouracil have FIGURE 13 | Summary of findings. DIO selectively supresses de novo FA synthesis and lipolysis in mammary adipose tissue, but increased lipogenesis and lipolysis in tumor tissue.…”
Section: Diet-induced Obesity Distinctly Alters Lipid Metabolism In Tmentioning
confidence: 99%
“…Treatment of N-myc proto-oncogene protein-amplified neuroblastoma cells with 10058-F4, an inhibitor of c-MYC/Max protein, a member of the basic helix–loop–helix leucine zipper family of transcription factors, triggers the accumulation of intracellular LDs as an outcome of mitochondrial dysfunction. The chemotherapeutic drugs doxorubicin and 5-fluorouracil (5-FU) in human colon carcinoma cells induce the accumulation of LDs as a result of up-regulated TG biosynthesis [ 192 , 202 ]. Hence, this points to a potential role for LDs as part of a general stress response to different classes of chemotherapeutic treatments.…”
Section: Lds In Chemotherapymentioning
confidence: 99%
“…Various media supplements such as amino acids, hormones, growth factors, and other co-factors are important in primary culture. Dulbecco's modified Eagle's medium (Cho et al, 2015;Nemoto, Sakurai, Tazawa, & Ishikawa, 1989;Nikoozad, Ghorbanian, & Rezaei, 2014;Wu et al, 2015;Zhang et al, 2014), Williams' E (Shibany, Totemeyer, Pratt, & Paine, 2016;Shri, Agrawal, Rani, Singh, & Onteru, 2017;Tomizawa et al, 2016b), Waymouth's MB (Rodriguez-Enriquez, Kai, Maldonado, Currin, & Lemasters, 2009), Ham's F12 (Rattanasinganchan et al, 2006;Sripa et al, 2005), RPMI 1640 (Horai et al, 2014;Khosravi, Shokri, & Eshghi, 2017;Mehdizadeh et al, 2017) and Leibovitz's 15 (L-15) (Anene, Rosenberg, Kleiner, Cornish, & Halushka, 2016;Mitaka, Sattler, & Pitot, 1991) are all available media formulations. Highly enriched media, which contain amino acid concentrations that are 5-10 times higher than most standard media, are superior for the maintenance of cell survival, preserving cellular protein levels and liver-specific functions (Gebhardt et al, 2003;Swift, Pfeifer, & Brouwer, 2010).…”
Section: Cultural Environment For Hepatocytesmentioning
confidence: 99%